Implementasi Kebijakan Pengembangan Karir Untuk Mewujudkan Efektivitas Kinerja Pada Kebijakan Penyetaraan Jabatan Di Lingkungan Pemerintah Kota Surabaya - Djamil, Moch.; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2024)
The Surabaya City Government in 2021 has carried out equalization of administrative positions into functional positions in accordance with PERMENPANRB No.17 of 2021 as an effort to simplify the bureaucracy. However, in the implementation process there is still a lack of employee understanding regarding the items of functional position activities and policies on career development. This study aims to analyze the implications of Career Development Policy to Realize Performance Effectiveness in the Equal Position Policy within the Surabaya City Government. This research uses a descriptive qualitative approach in answering problems. This research uses a case study research design with literature studies and interview techniques with 4 informants who are ASN employees within the Surabaya City Government. The results of the study show that the facts on the ground describe the unpreparedness of ASN and the City Government of Surabaya in implementing the Equalization Policy of PERMENPANRB No.17 of 2021 concerning Equalization of Administrative Positions into Functional Positions in the Surabaya City Government Environment using the CIPP evaluation model, indicating that the implementation of these regulations has been quite good in terms of context, input, process, and product, although there are still some deficiencies that need to be corrected. Keywords: Career Development Policy, Performance Effectiveness, Position Equalization Policy